2014
DOI: 10.1177/1535370213517616
|View full text |Cite
|
Sign up to set email alerts
|

STARD6 is expressed in steroidogenic cells of the ovary and can enhance de novo steroidogenesis

Abstract: STARD6 is a member of the StAR-related lipid transfer (START) domain family of proteins whose function thus far remains obscure. While it recently was shown to facilitate steroidogenesis in a cell-free setting, it has not been localized to steroidogenic cells of normal reproductive tissues. In a recent microarray study, we detected STARD6 mRNA in cultured porcine ovarian granulosa cells which are steroidogenic. In the present study, we examined regulation of STARD6 mRNA in porcine granulosa cultures, and found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
(51 reference statements)
0
4
0
1
Order By: Relevance
“…In addition, its expression in testes decreases with ageing and may be associated with decreased spermatogenesis in aged rats 61 . By analogy, in the pig ovary, STARD6 is differentially expressed during the estrous cycle, in the mid-luteal phase corpora lutea 71 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, its expression in testes decreases with ageing and may be associated with decreased spermatogenesis in aged rats 61 . By analogy, in the pig ovary, STARD6 is differentially expressed during the estrous cycle, in the mid-luteal phase corpora lutea 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Transcripts of all enzymes in the mevalonate pathway for the production of cholesterol were significantly upregulated in the presence of high extracellular amino acid concentrations (fold changes from 2 to 6) [10], while transcripts of enzymes involved in the final conversion to biologically active forms of sex steroids showed overall lower magnitudes, although yet significant upregulations (1.5–3 fold; the “Results” section). Similar differences in transcript levels were also displayed by genes related to intracellular cholesterol trafficking or transfer of cholesterol to inner mitochondrial membranes, where StarD6 is reported to interact with the mitochondrial membrane moving cholesterol from outer to inner mitochondrial membranes, necessary for initiation of steroid synthesis [19, 20]. It was thus appealing to suggest that amino acids may induce de novo steroid biosynthesis in muscle cells.…”
Section: Discussionmentioning
confidence: 93%
“…Both STARD1 and STARD6 unfold and refold with similar (slow) kinetic patterns, and interact equally well with mitochondrial membranes [149]. Initially STARD6 was reported to be limited to male germ-line cells [84,150,151], but recent studies have shown that this protein is expressed in steroidogenic cells of the ovary, where it lies under the control of GATA4 and GATA6 transcription factors, and facilitates pregnenolone production [150]. Further, Chang and coworkers have reported STARD6 to be present in the brain, spinal cord and dorsal root ganglia, where it may play a role in the formation of neuroprotective steroids after excitotoxic brain injury [151][152][153].…”
Section: Sterol-binding Proteins: Cytosolicmentioning
confidence: 99%